Aspectos genéticos do metabolismo lipídico e risco para colelitíase na obesidade mórbida após cirurgia bariátrica - Pinheiro Júnior, Sidney (2012)
Background Outstanding, among the factors associated to cholelithiasis after bariatric surgery, are those related to metabolism and synthesis of lipoproteins, such as apolipoprotein E (ApoE) and protein from cholesterol ester transfer protein (CETP). Methods - 220 patients have been part of the study, 114 (G1) with cholelithiasis postoperatively and 106 (G2) without cholelithiasis in over 8 months period, including the analysis of apoE-Hha I and CETP-TaqIB polymorphisms per PCR / RFLP and biochemical profile [total cholesterol (TC), lipoprotein cholesterol fraction of low (LDL), high (HDLc) and very low density (VLDLc), triglycerides (TG) and glucose levels. It was accepted level of significance for P <0.05. Results - Preoperatively, it was observed that in G1 54% of the patients with the APOE*4 allele had serum altered levels of LDL. Postoperatively, there was a decrease (P <0.001) of LDL with TG in G2 (85.3 ± 32.1 mg / dL, P <0.0001) and glucose (G1 = 83.2 ± 10.7 mg / dL; G2 = 84.7 ± 11.5 mg / dL, P <0.0001 for both), TC and LDL and HDL cholesterol increased only in G2 (P <0.0001). The B1 allele was related to decreased (P <0.01) of TC, LDLc and TG postoperatively in both groups, in addition to lowering glucose levels and increase HDL cholesterol only in G2 (P <0.0001). The genotype APOE*_/4 in G2 was associated with decreased levels of TC, LDL, TG and glucose levels and increased levels of HDL cholesterol (P<0.01) postoperatively. Conclusions - This study does not confirm the association of apoE-Hha-I and CETP-TaqIB with gallstones in the late postoperative period after bariatric surgery. However, B1 allele seems to enhance the action of bariatric surgery in the control of dyslipidemia effectively reducing levels of TC, LDL and TG, with additional benefit to those without gallstones by decreasing blood glucose levels and also increase HDL cholesterol. The relationship of APOE*4 with increased LDLc preoperatively only in G1 suggests its association with cholelithiasis in the late postoperative bariatric surgery, which should be evaluated in prospective studies.